Analisis Kekuatan dan Deformasi Rangka Tubular Space Frame Mobil Listrik Megathrust Electric dengan Variasi Dimensi Serta Material Menggunakan Metode Finite Element Analysis (FEA) - Adityo Adityo; Wanda Afnison; Waskito Waskito; Delima Yanti Sari (Jurnal Vokasi Mekanika (VoMek), 2025)
The development of electric vehicles in Indonesia has grown rapidly, supported by the Indonesian Electric Car Competition (KMLI) which encourages innovation in designing lightweight yet strong vehicle frames. The tubular space frame of the “Megathrust Electric” car previously used ASTM A36 steel with a total weight of 32 kg, which was considered inefficient as it increased power consumption and reduced overall performance. This study aims to analyze the effect of pipe dimension variations and alternative materials, namely Aluminium alloy 6061 and 6063, on the strength and deformation of the frame. The method employed is Finite Element Analysis (FEA) using SolidWorks software under static loading conditions that represent real operating scenarios. The pipe variations examined include 19.05 mm diameter with 2.5 mm thickness and 25.4 mm diameter with 2 mm thickness. The simulation results show that the 25.4 × 2 mm Aluminium alloy 6061 configuration provides the best structural performance with a maximum stress of 55.07 MPa, deformation of 1.583 mm, and a safety factor (FOS) of 5.012. In contrast, the 19.05 × 2.5 mm Aluminium alloy 6063 configuration is lighter but exhibits higher stress (184.4 MPa) and a lower safety factor (1.161). Therefore, the Aluminium Alloy 6061 pipe with 25.4 mm diameter is recommended as the optimal frame design, offering a balance between strength, stiffness, and weight efficiency to support the performance of electric vehicles in competition.